CHARACTERISTICS OF LOW BACK PAIN IN NEUROLOGY OUTPATIENT - Arnetha, Tiffani Shavira; Devy, Monica Sari; Payangan, Natan (PERDOSNI (Perhimpunan Dokter Spesialis Neurologi Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Introduction: Low back pain is a significant global health issue. This condition not only causes physical discomfort but can also reduce the quality of life and productivity of individuals. This study aims to determine the characteristics of patients with low back pain at Mampang Prapatan General Hospital. Methods: This study was a descriptive cross-sectional study using secondary medical record data from Mampang Prapatan General Hospital in 2024. The sampling technique used in this study was simple random sampling. Results: There were 40 samples in this study, 31 samples were female (77.5%) and 9 samples were male (22.5%). The average age was 55.6 years old, with the largest age group being those over 60 years old (42.5%). The most common nutritional status was grade 1 obesity (47.5%). Radiating pain was most frequently reported pain (67.5%). Radiological examination using lumbosacral x-ray showed that the most common finding was lumbar spondylosis (57.5%). The most commonly used treatment was a combination of pharmacological and non-pharmacological therapy, specifically physiotherapy combined with analgesics and anti-spasmodic drugs. Conclusion: It can be concluded that the distribution of low back pain patients at Mampang Prapatan General Hospital were most prevalent among females, elderly individuals (>60 years), had obese nutritional status, and experienced radiating pain symptom. A combination of pharmacological and non-pharmacological management can be used to improve the quality of life for patients with low back pain.